Menilai pertumbuhan dan trend pada studi sustainable development goals: Analisis bibliometrik - Supami Wahyu Setiyowati; Fauzan Fauzan; Susmita Dian Indiraswari (Jurnal Ekonomi Modernisasi, 2022)
Scientific production on the Sustainable Development Goals has grown in recent years. However, there is still little research that provides a global picture of this topic. The purpose of research is to identify research trends and scientific production from time to time. Bibliometric analysis was used to analyze a sample of 3608 articles published between 1996 and 2022. Sustainable Development Goals is a query used in article titles to obtain metadata from the Scopus bibliographic database. Microsoft excel was used to perform frequency analysis, VOSviewer for data visualization and Harzing's Publish or Perish was used for citation metrics. The results show that there is an increase in the literature on the Sustainable Development Goals from 1996 to 2022, and a significant increase since 2016. There have been various studies involving multi-author collaboration published in multiple languages, with a total of 32 authors. from 141 different countries and 32 institutions. The United States was the largest contributor to this study. Most publications are published by Sustainability Switzerland. These findings could aid future research related to the overview of Sustainable Development Goals research around the world over time.